Association between dietary inflammatory index and metabolic syndrome: Analysis of the NHANES 2005–2016 - Zhang, Xiaochen; Guo, Yinpei; Yao, Nan; Wang, Ling; Sun, Mengzi; Xu, Xiaomeng; Yang, Huanshuai; Sun, Yang; Li, Bo (Frontiers in Nutrition, 2022)
Objective: Metabolic syndrome (MetS) is a global problem that increasingly violates human health and quality of life. We explored the relationship between dietary inflammatory potential represented by dietary inflammatory index (DII) and the occurrence of MetS to provid data support for the prevention of it through dietary structure intervention. Methods: The data was come from National Health and Nutrition Examination Survey 2007-2018, including demographic, dietary, questionnaire variables and laboratory indicators. MetS was defined according to the criteria proposed by the American Endocrine Association (ACE) and the American Society of Clinical Endocrinology (ACCE). DII was calculated using the scoring method established by Shivappa. We divided DII scores into 4 quartiles, the chi-square test was used to compare the variable difference between DII quartiles groups. A logistic regression model was used to analyze the association between DII and MetS. We also performed subgroup analysis. A generalized linear regression model was used to explore the association of DII level and the levels of seven MetS related biochemical indicators. Results: The final sample size was 8180, and the DII scores of the subjects were -5.50 ~ 5.22. The proportions of men, young people, non-Hispanic blacks, poor people, smokers, and MetS patients in the Q1~Q4 DII quantiles groups were gradually increased. The risk of MetS in the Q4 group which had highest dietary inflammatory degree was 1.592 (1.248, 2.030) times higher than that in the Q1 group respectively (P＜0.001). After subgroup analysis, women, youth, non-smokers and alcohol drinkers were found to be more sensitive to the dietary inflammation. Then we found that the level of DII was significantly positively correlated with waist circumference (WC), body mass index (BMI), triglyceride (TG), systolic blood pressure (SBP) and diastolic blood pressure (DBP), but negatively correlated with high density lipoprotein cholesterol (HDL-C). Conclusions: In the research subjects, the degree of dietary inflammation was associated with the occurrence of MetS and significantly affected WC, BMI, blood pressure, and blood lipid levels. It is necessary to conduct investigations and early dietary interventions for women and young people to prevent the occurrence of chronic metabolic diseases.